2016
DOI: 10.1016/j.ces.2016.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat treatment on the atomic structure and surface energy of rutile and anatase TiO2 nanoparticles under vacuum and water environments

Abstract: 10Nanomaterials have become a widely used group of materials in many chemical engineering 11 applications owing to their ability to provide an enhanced level of functional properties 12 compared to their crystalline and bulk counterparts. Here we report fundamental level 13 advancements on how the anatase and rutile phase of TiO2 nanoparticles chemo-thermally 14 respond between room temperature and the melting temperature under both vacuum and water 15 environments. The current study is based on using molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 54 publications
(6 reference statements)
2
11
0
Order By: Relevance
“…Experimental unit cell parameters and space group for anatase (Horn et al, 1972;Naicker et al, 2005) The typical average length (L):diameter (D) ratio of nanowires used in previous experiments range between about 10:1 and 20:1 (Shirale et al, 2010;Moshofsky and Mokari, 2013;Gudiksen et al, 2001), however here, this ratio is limited to 6:1 due to computational restrictions on the total number of atoms. The information obtained from the current simulations is useful and indicative of the nano scale properties of TiO2 in different shapes (Okeke et al, 2016). The sizes of the particles and their corresponding number of Ti and O atoms are presented in Table 2.…”
Section: Tablementioning
confidence: 91%
See 4 more Smart Citations
“…Experimental unit cell parameters and space group for anatase (Horn et al, 1972;Naicker et al, 2005) The typical average length (L):diameter (D) ratio of nanowires used in previous experiments range between about 10:1 and 20:1 (Shirale et al, 2010;Moshofsky and Mokari, 2013;Gudiksen et al, 2001), however here, this ratio is limited to 6:1 due to computational restrictions on the total number of atoms. The information obtained from the current simulations is useful and indicative of the nano scale properties of TiO2 in different shapes (Okeke et al, 2016). The sizes of the particles and their corresponding number of Ti and O atoms are presented in Table 2.…”
Section: Tablementioning
confidence: 91%
“…Also, the radial distribution functions (RDF's) of the nanoparticles were linked to the variation of potential energy of the system with temperature. It was observed that changes in the gradient of a plot of potential energy versus temperature associated with the melting transition occurred at temperatures similar to those associated with the broadening of peaks in the RDFs (Okeke et al, 2016).…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations